Evaluation of the efficacy and safety of a standardised intracameral combination of mydriatics and anaesthetics for cataract surgery. Issue 7 (3rd November 2015) - Labetoulle, Marc; Findl, Oliver; Malecaze, François; Alió, Jorge; Cochener, Béatrice; Lobo, Conceição; Lazreg, Sihem; Hartani, Dahbia; Colin, Joseph; Tassignon, Marie-José; Behndig, Anders
Abstract : Background/aims: To compare the efficacy and safety of intracameral (IC) administration at the beginning of cataract surgery, of Mydrane, a standardised ophthalmic combination of tropicamide 0.02%, phenylephrine 0.31% and lidocaine 1%, to a standard topical regimen. Methods: In this international phase III, prospective, randomised study, the selected eye of 555 patients undergoing phacoemulsification with intraocular lens (IOL) implantation received 200 μL of Mydrane (Mydrane group) just after the first incision or a topical regimen of one drop each of tropicamide 0.5% and phenylephrine 10% repeated three times (reference group). The primary efficacy variable was achievement of capsulorhexis without additional mydriatics. The non-inferiority of Mydrane to the topical regimen was tested. The main outcome measures were pupil size, patient perception of ocular discomfort and safety. Results: Capsulorhexis without additional mydriatics was performed in 98.9% of patients and 94.7% in the Mydrane and reference groups, respectively. Both groups achieved adequate mydriasis (>7 mm) during capsulorhexis, phacoemulsification and IOL insertion. IOL insertion was classified as 'routine' in a statistically greater number of eyes in the Mydrane group compared with the reference group (p=0.047). Patients in the Mydrane group reported statistically greater comfort than the reference group before IOL insertion (p=0.034). Safety data were similar between groups. Conclusions: Mydrane is an effective and safe alternative to standard eye drops for initiating and maintaining intraoperative mydriasis and analgesia. Patients who received IC Mydrane were significantly more comfortable before IOL insertion than the reference group. Surgeons found IOL insertion less technically challenging with IC Mydrane. Trial registration number: NCT02101359; Results.